2021
DOI: 10.1186/s40561-021-00161-y
|View full text |Cite
|
Sign up to set email alerts
|

An artificial intelligence approach to monitor student performance and devise preventive measures

Abstract: A major problem an instructor experiences is the systematic monitoring of students’ academic progress in a course. The moment the students, with unsatisfactory academic progress, are identified the instructor can take measures to offer additional support to the struggling students. The fact is that the modern-day educational institutes tend to collect enormous amount of data concerning their students from various sources, however, the institutes are craving novel procedures to utilize the data to magnify their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 35 publications
0
26
0
1
Order By: Relevance
“…It increases their learning interest (Lin & Chang, 2020), facilitates interactive learning environments via particular tools like Smart Sparrow that promote learner engagement with educational content (Karsenti, 2019). Numerous studies have also demonstrated substantial improvements in academic performance through the aid of AI technologies (Khan et al, 2021;Kim et al, 2021). It significantly improves learning outcomes and student happiness (Winkler & Söllner, 2018), maximizing student learning abilities and achievement (Clarizia et al, 2018).…”
Section: Potential Benefits For Studentsmentioning
confidence: 99%
“…It increases their learning interest (Lin & Chang, 2020), facilitates interactive learning environments via particular tools like Smart Sparrow that promote learner engagement with educational content (Karsenti, 2019). Numerous studies have also demonstrated substantial improvements in academic performance through the aid of AI technologies (Khan et al, 2021;Kim et al, 2021). It significantly improves learning outcomes and student happiness (Winkler & Söllner, 2018), maximizing student learning abilities and achievement (Clarizia et al, 2018).…”
Section: Potential Benefits For Studentsmentioning
confidence: 99%
“…Evaluation of the performance of the prediction model was carried out using a confusion matrix [7]. The performance measure was based on the confusion matrix that is usually used is accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The performance measure was based on the confusion matrix that is usually used is accuracy. Accuracy is the ratio between the number of correctly predicted results compared to the number of data [1], [7]. Calculation of accuracy can be done using (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But it failed to consider more information on students' performance to possibly predict their performance using deep learning approaches. The effectiveness of machine learning algorithms was estimated in [6] A deep neural network (DNN) was introduced in [7] to enhance the predictive approaches for students' academic performance. But the performance of accuracy of prediction was not improved.…”
Section: Introductionmentioning
confidence: 99%